Molecular identification and microbiome profiling of household casebearer, Phereoeca sp. (Lepidoptera: Tineidae) from Malaysia: Potential implications for human skin irritation - Salmah Yaakop; Muhammad Afiq Senen; Nur Alya Adila Rosli; Muhamad Azmi Mohammed (PLoS ONE, 2026)
In Malaysia, anecdotal accounts have linked the household casebearer (Lepidoptera: Tineidae) to skin lesions and localized inflammation; however, scientific evidence is lacking, and the species’ taxonomic identity remains unclear. This study aimed to confirm the species identity and examine the bacteria associated with larvae that may be linked to skin irritation. Larvae were collected from three locations in Peninsular Malaysia and preserved. DNA was extracted from the larvae, and species identification was conducted by analyzing the cytochrome c oxidase subunit I (COI) gene through DNA barcoding. To study the bacteria present, the bacterial 16S rRNA gene was amplified and sequenced using Next-generation sequencing technology. The DNA sequences were analyzed to determine the species and profile the bacterial communities. The results identified the specimens as Phereoeca sp., suggesting they may represent an undescribed lineage. Microbiome analysis revealed that Proteobacteria (40.18%) and Actinobacteriota (32.13%) were the dominant bacterial phyla, with Cutibacterium acnes , Enterobacter , and Pseudomonas among the taxa previously associated with skin irritation or opportunistic infections. Several unclassified but potentially relevant taxa were also identified. These findings provide new insights into the microbial ecology and taxonomy of Phereoeca and underscore its potential role in medically significant interactions within human environments.